The Effectiveness of BP4's Role in Addressing the High Divorce Rate (Case Study at the KUA Pontianak Barat District) - Gefi Melyana Saputri; Ismi Tartila; Fatimatuz Zahro (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Divorce is a social problem that has a major impact on individuals and society. In West Pontianak District, the high divorce rate is causing concern, so it is important to evaluate the mitigation efforts carried out by BP4 (Marriage Development and Preservation Advisory Agency). This research aims to measure the effectiveness of BP4's tasks in overcoming the high divorce rate in KUA West Pontianak District. The main focus of the research is on the strategies and approaches used by BP4 and the outcomes of their interventions. This research uses a qualitative descriptive method to understand in depth the role and effectiveness of BP4. Data was collected through interviews with BP4 staff and couples who had received guidance, as well as through observation and analysis of related documents.